Planning for the Development Program of Village-Owned Enterprises (BUMDes) in Sumedang Regency - Dadan Setia Nugraha (Universitas Medan Area, 2023)
This research aims to examine the development program planning of Village-Owned Enterprises (BUMDes) in the Community Empowerment and Village Agency of Sumedang Regency. The research report is prepared using a descriptive qualitative method. The sampling technique used is purposive sampling, involving four key informants: the Functional Division, the Financial Sub-Division, and the Pepkades Sub-Division (two individuals from each division). Data collection techniques involve literature and field studies. Data analysis uses the Miles and Huberman method, including data reduction, data presentation, conclusion/verification, and triangulation. The research results show that the role of the Sumedang Regency Government, through the Community Empowerment and Village Agency, is involved in planning related to BUMDes empowerment programs. However, the implementation of this planning is still not optimal due to challenges in human resource management in BUMDes. Intensive efforts are needed to provide coaching and socialization related to BUMDes development programs, organize regular coordination meetings between the Agency and BUMDes Managers, and conduct periodic performance evaluations of BUMDes management.